1998
DOI: 10.1021/jp983358e
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry and Kinetics of Silicon Hydride Cluster Formation during Thermal Decomposition of Silane

Abstract: Product contamination by particles nucleated within the processing environment often limits the deposition rate during chemical vapor deposition processes. A fundamental understanding of how these particles nucleate could allow higher growth rates while minimizing particle contamination. Here we present an extensive chemical kinetic mechanism for silicon hydride cluster formation during silane pyrolysis. This mechanism includes detailed chemical information about the relative stability and reactivity of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(214 citation statements)
references
References 61 publications
(120 reference statements)
6
206
0
2
Order By: Relevance
“…The gas-phase species equations were also fully coupled to the particle growth by properly accounting for species depletion as a result of surface reactions (Girshick et al, 2000). Chemical nucleation of particles is based on a chemical clustering model (Swihart & Girshick, 1999), in which the basic mechanism includes reversible chemical reactions between silicon/hydrogen molecules containing up to ten silicon atoms. The nucleation rate is taken to be the rate at which these chemical reactions irreversibly produce molecules containing more than ten silicon atoms.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The gas-phase species equations were also fully coupled to the particle growth by properly accounting for species depletion as a result of surface reactions (Girshick et al, 2000). Chemical nucleation of particles is based on a chemical clustering model (Swihart & Girshick, 1999), in which the basic mechanism includes reversible chemical reactions between silicon/hydrogen molecules containing up to ten silicon atoms. The nucleation rate is taken to be the rate at which these chemical reactions irreversibly produce molecules containing more than ten silicon atoms.…”
Section: Theorymentioning
confidence: 99%
“…A detailed chemical clustering model was previously developed for chemical nucleation of silicon hydrides containing up to ten silicon atoms (Swihart & Girshick, 1999), and that model was used here. The clustering model includes detailed information regarding the thermodynamic properties and reactivities of silicon hydride clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of silane decomposition kinetics have been reported (Becerra and Walsh 1992;Ho et al 1994;Moffat et al 1992a, b;Purnell and Walsh 1984;Wong et al 2004). As in Dang and Swihart (2008), this work used an extensive chemical kinetic mechanism for silicon hydride cluster formation during silane pyrolysis (Swihart and Girshick 1999). This reaction mechanism includes 133 gas phase species with a critical size of 10 silicon atoms.…”
Section: Cfd Simulationmentioning
confidence: 99%
“…Second, the reaction zone was simulated using an axisymmetric two-dimensional MPSalsa model, whose boundary conditions were obtained from the first step. Last, a two-dimensional aerosol dynamics model, with boundary layer approximations, was used to study the silicon nanoparticle formation using more complete silane decomposition chemistry (Swihart and Girshick 1999), together with the temperature and velocities extracted from the 2D reaction zone CFD simulation. A bivariate moment model with finite coalescence rate was applied, allowing realistic predictions of particle morphology.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation